Emergence as a science - Lichtenstein, Benyamin (Frontiers in Complex Systems, 2025)
Although this Special Issue calls for a theory of emergence, the present paper argues that the breadth of the phenomenonrequires a science, within which various theories can be explored and tested. To identify a structure for such a science of emergence, I pursued an in-depth cross-disciplinary analysis of emergence and its emergents. The result was identifying 9 emergence Prototypes, each of which reflects a unique aspect or context of emergence. Further, within some Prototypes, decades of scientific research has led to one or more Principles that its scholars ascribe to. Finally, the potential of an emergence science is explored by introducing applications of emergence to Leadership, Entrepreneurship, and Sustainability.